A LiteMP4Repair: Corrupted MP4 Repair Using Header Substitution Tool - Nur Sabrina Salim; Kamaruddin Malik Mohamad (Applied Information Technology And Computer Science, 2021)
In digital forensic, recovery of deleted and damaged video file plays an important role in searching for evidences. In this paper, LiteMP4Repair tool is proposed to repair the corrupted videos. LiteMP4Repair tool are focusing on corrupted file header in MP4 file. Moreover, LiteMP4Repair tool will substitute the corrupted header with multiple random different headers. The final product for the tool is the corrupted video will be playable. Object-Oriented System Development is used as the methodology for flexibility to the developer. In order to complete the developer, the Microsoft Visual Studio 2019 with C# programming language and PhpMyAdmin Database is chosen as the development tool.